Trustworthy Predictive Algorithms for Complex Forest System Decision-Making - Rana, Pushpendra; Varshney, Lav R. (Frontiers in Forests and Global Change, 2021)
Advances in predictive algorithms are revolutionizing how we understand and design effective decision support systems in many sectors. The expanding role of predictive algorithms is part of a broader movement towards using data-driven machine learning (ML) for modalities including image, natural language, and speech. This article reviews whether and to what extent predictive algorithms can assist decision-making in forest conservation and management. Although state-of-the-art ML algorithms provide new opportunities, adoption has been slow in forest decision-making. This review shows how domain-specific characteristics, such as system complexity, impose limits on using predictive algorithms in forest conservation and management. We conclude with possible directions for developing new predictive tools and approaches to support any meaningful forest decisions through easily interpretable and explainable recommendations.